Factors influencing the contribution of cash waqf among KAFA teachers in Jitra - Mohd Iqbal Azamuddin, Mohd Zawizaz (2025)
This study extends the Theory of Planned Behaviour (TPB) to examine the intention of KAFA teachers in Kedah to participate in cash waqf. Cash waqf, a form of Islamic endowment, plays a crucial role in socioeconomic development, yet participation remains low in Malaysia, particularly in Kedah. The study investigates four key determinants (attitude, subjective norms, perceived behavioural control, and religiosity) affecting waqif intention. A quantitative research approach was adopted, utilizing a structured questionnaire distributed to KAFA teachers in Jitra, Kedah. The data were analyzed using multiple regression analysis to determine the relationships between the independent variables and waqif intention. The findings reveal that religiosity and attitude significantly influence the intention to contribute to cash waqf, whereas subjective norms and perceived behavioural control have a moderate impact. These results highlight the need for enhanced awareness programs, improved institutional trust, and digital platforms to facilitate cash waqf contributions. The study contributes to the academic discourse on Islamic finance by providing insights into behavioural factors influencing cash waqf participation, particularly among educators who play a pivotal role in shaping community values.